2020
DOI: 10.1177/1464884920922006
|View full text |Cite
|
Sign up to set email alerts
|

A first-person promise? A content-analysis of immersive journalistic productions

Abstract: Major news outlets increasingly use immersive techniques in their journalistic productions. The idea is that, through the application of immersive technologies, the news consumer can engage with and be part of the story. However, we do not know, to what extent this promise is actually fulfilled in productions currently accessible to news audiences. This study uses a multi-step approach to fill this knowledge gap. First, based on an interdisciplinary literature review, we propose a conceptual model of immersive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 41 publications
1
8
0
3
Order By: Relevance
“…Analysis matrix designed for the study. Source: created by authors based on previous studies Stories TopicBenítez and Herrera 2019;de Bruin et al 2020) Purpose of the video(Benítez and Herrera 2019) Genre/narrative form(Watson 2017;Jones 2017) Fig.1360°videos published by humanitarian organizations per year (from 2015 to April 2019). Source: authors' compilation people or refugees, as seen in productions such as Mediterranean Rescue Operation, Ali's Story or We Are Rohingya.…”
mentioning
confidence: 99%
“…Analysis matrix designed for the study. Source: created by authors based on previous studies Stories TopicBenítez and Herrera 2019;de Bruin et al 2020) Purpose of the video(Benítez and Herrera 2019) Genre/narrative form(Watson 2017;Jones 2017) Fig.1360°videos published by humanitarian organizations per year (from 2015 to April 2019). Source: authors' compilation people or refugees, as seen in productions such as Mediterranean Rescue Operation, Ali's Story or We Are Rohingya.…”
mentioning
confidence: 99%
“…First-time media explorations in immersive journalism tend to be timid and limited, especially in terms of interactivity, with the user acting primarily as an observer (De-Bruin et al, 2020). However, this study makes it clear that the main value of immersive technologies as applied to journalism is the sense of presence, so the place takes on an indisputable protagonism, as other authors have also previously observed (Kukkakorpi;Pantti, 2020).…”
Section: Discussionmentioning
confidence: 57%
“…For De- Bruin et al (2020), the four main elements of immersive journalism are: 1) immersive technologies; 2) immersive features in the narrative; 3) interaction or agency possibilities for the user; and 4) the outcome of sense of presence and emotional engagement.…”
Section: Introductionmentioning
confidence: 99%
“…Uma abordagem de pesquisa que ainda necessita de investigações, sobretudo de abordagem qualitativa (pouco realizada), são os estudos sobre consumo de IJ. Das referências mapeadas sobre consumo em Rocha (2021), encontramos Wang, Gu & Suh (2018), Steinfeld (2019), Kang et al (2019), De Bruin et al (2020, e . Na análise da rede de palavras 2020, o termo "consumo" e "audiência" já indicam essa abordagem, dos seis trabalhos sobre consumo três foram realizados em 2020.…”
Section: O Jornalismo Imersivo De Eva Domínguez: Matriz Teórica Da Im...unclassified
“…Entre 2015 a 2016, foram publicados relatórios analíticos e de previsão para o futuro da produção imersiva no Jornalismo (Aronson-Raht et al, 2015;Doyle, Gelman & Gill, 2016;Sirkkunen et al, 2016;Watson, 2017). Entre 2016 a 2019, importantes pesquisas foram publicados sobre o objeto de estudo com abordagens distintas: i) estudos teóricos sobre os diferentes elementos (imersividade, empatia, experiência, interação, tecnologia, etc) do IJ (Sirkkunen et al 2016;Sánchez Laws, 2017;Hardee & McMahan, 2017;Costa, 2017;Longhi & Caetano, 2019;Toursel & Useille, 2019;Jones, 2017;Paíno & Rodríguez, 2019a); ii) análises robustas sobre conteúdos jornalístico imersivos e informativos gerados pelos meios de comunicação afim de levantar classificações de gêneros jornalísticos imersivos (Benítez & Herrera, 2017;Colussi & Reis, 2020;Paíno & Rodríguez, 2019b;iii) ética no Jornalismo Imersivo (Pérez-Seijo & López-García, 2019; Sánchez Laws & Utne, 2019); iv) e consumo de Jornalismo Imersivo (Wang, Gu & Suh, 2018;Steinfeld, 2019;Kang et al 2019;De Bruin et al, 2020;Rocha, 2021).…”
Section: Introductionunclassified